23 Assessment of the ischaemic burden in patients with ischaemic heart disease through combined high-resolution assessment of quantitative perfusion and late enhancement. (18th April 2016) - Villa, ADM; Sammut, E; Shome, JS; Plein, S; Razavi, R; Chiribiri, A
Abstract : Background: Patients with ischaemic heart disease (IHD) often show a combination of inducible ischaemia and previous myocardial infarction, therefore is particularly relevant to reach an accurate assessment of myocardial viability and ischaemic burden, as this may results in more appropriate therapy and better outcome. Areas of scar frequently result in false-positive perfusion findings, we therefore hypothesised that combined cardiac magnetic resonance (CMR) high-resolution quantitative perfusion and late gadolinium enhancement (LGE) protocol will result in a more accurate evaluation of ischaemic burden, avoiding areas of scar. Methods: 15 patients with IHD and ejection fraction (EF) <45% were included. Patients underwent adenosine stress perfusion at 3T (Philips Achieva) using high-resolution kt turbo-field-echo sequence and dual bolus approach. Perfusion and LGE images were analysed both qualitatively and quantitatively (using validated high-resolution deconvolution analysis and conventional semi-quantitative analysis with 5SD). For combined analysis, perfusion and LGE images were matched in terms of position and cardiac phase using a deformable template segmentation method. High-resolution MPR and LGE maps were then generated and ischaemic burden calculated ±LGE (Figure 1 ). Results: The average EF was 33 ± 9.5%. All patients showed scar and perfusion defects at visual assessment. The average scarred area was 18 ± 6.8%. Average MPR was 2.3 ± 2.4, 3.2 ± 0.6 in viable area (LGE-) and 1.05 ± 0.69 in non-viable areas (LGE+) (p = 0.001 Vs LGE-). 27%(4/15) of patients had a perfusion defect extending only in LGE area. The overall ischaemic burden (MPR threshold 1.5) was 23.2 ± 13.5%, but after excluding LGE dropped to 12.4 ± 7.6% (p = 0.001). Conclusions: Our study demonstrates the potential of combined high-resolution assessment of stress perfusion and LGE to provide more accurate measurements of ischaemic burden excluding areas of scar, These areas, which frequently result in false positive perfusion defects and possible overestimation of ischaemic burden, had an MPR≤1, as expected in areas of scar.